Non-Cardiovascular Comorbidities as Evaluated by Elixhauser Comorbidity Score in Individuals Undergoing TAVR. Issue 5 (3rd September 2019) - Nagaraja, Vinayak; Cohen, Mauricio G.; Suh, William; Alasnag, Mirvat; Genereux, Philippe; Potts, Jessica; Gunning, Mark; Nolan, Jim; Bagur, Rodrigo; Mamas, Mamas A.
ABSTRACT: Background: To explore the relationship between comorbidity burden and mortality, peri-procedural complications, and length of stay in patients treated with TAVR in the National Inpatient Sample (NIS). Patients undergoing transcatheter aortic valve replacement (TAVR) often have multiple comorbidities. Whilst the impact of individual comorbid conditions on clinical outcomes following TAVR has been previously assessed, the impact of more global measures of comorbidity remains unknown in this cohort. To explore the relationship between comorbidity burden and mortality, peri-procedural complications, and length of stay in patients treated with TAVR NIS. Methods: TAVR procedures were identified between 2011 and 2014 and comorbidities were defined by the Elixhauser classification system (ECS) consisting of 30 comorbidity measures. Endpoints included in-hospital mortality, periprocedural complications, and length of stay. Patients were classified based on their ECS in five categories (ECS I < 0, ECS II = 0, ECS III = 1–5, ECS IV = 6–13, ECS V ≥ 14). Results: A total of 40, 604 TAVR patients were identified. Mean age was 81.2 ± 8.5 years. Patients with ECS category V accounted for more than 40% of the cohort and experienced almost a 2.5-fold increase in in-hospital mortality (OR 2.42, 95% CI: 1.28–4.56), acute kidney injury (OR: 6.23, 95% CI: 4.13–9.41), major bleeding (OR: 2.26, 95% CI: 1.71–2.99), post-procedural stroke or TIA (OR: 2.02, 95% CI: 1.08–3.78). It was also associated with a mean 4.14-day increased length of stay (95% CI: 3.67 to 4.65) compared to patients with lower ECS category after adjusting for confounding factors. Conclusions: Our study of over 40, 000 TAVRs shows that Elixhauser comorbidity score was independently associated with higher mortality, periprocedural complications, and length of stay. Global comorbidity burden is an important consideration for risk stratification in patients undergoing TAVR.